معالم منهج الإسلام الحضاري: روية مقاصدية = Maálim manhaj al-Islam al-hadhari: ruýah maqasidiyah - Laeba, Muhammad (2008)
The Islam Hadhari approach has been widely debated recently, especially in Malaysia where the government has adopted a developmental project with this name. This project was initiated by the current Prime Minister Mr Abdullah Badawi when he proposed this project in a speech before his ruling party in 20003. Some have raised certain objections about the name and content of the approach. This paper clarifies the term Islam Hadhari and its objectives, linking the whole approach to the concept of Maqasid (objectives), and studying it through the perspective of Maqasid